2016
DOI: 10.1007/s13197-016-2387-5
|View full text |Cite
|
Sign up to set email alerts
|

Use of response surface methodology to investigate the effects of brown and golden flaxseed on wheat flour dough microstructure and rheological properties

Abstract: The aim of this study was to assess the effects of brown flaxseed and golden flaxseed on the water absorption and the rheological parameters of wheat flour. The rheological properties were evaluated by the Mixolab. The optimum parameters were identified for high quality flaxseed-wheat composite flour bread. Each predictor variable was tested at five levels. The microstructure of dough was assessed by epifluorescence light microscopy. The substitution of 4.81/100 g for brown flaxseed and 5.07/ 100 g for golden … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 30 publications
5
22
0
Order By: Relevance
“…The statistical significance of the linear term of GPF level addition in RWF as well of its quadratic term shows a higher effect of this factor on the dough ST. A decrease of dough ST with the GPF level increase can be related to the gluten dilution as a result of an addition of nongluten flour like GPF. Similar results were reported for flaxseed flour (Codină & Mironeasa, ) at high levels of flaxseed addition, the gluten matrix presenting physical disruption which can cause dough weakening. The results obtained are in accord to others previously reported (Bono, ; Mironeasa et al, ), revealing that GPF added in wheat flour leads to a decrease of dough ST with the addition level increase.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The statistical significance of the linear term of GPF level addition in RWF as well of its quadratic term shows a higher effect of this factor on the dough ST. A decrease of dough ST with the GPF level increase can be related to the gluten dilution as a result of an addition of nongluten flour like GPF. Similar results were reported for flaxseed flour (Codină & Mironeasa, ) at high levels of flaxseed addition, the gluten matrix presenting physical disruption which can cause dough weakening. The results obtained are in accord to others previously reported (Bono, ; Mironeasa et al, ), revealing that GPF added in wheat flour leads to a decrease of dough ST with the addition level increase.…”
Section: Resultssupporting
confidence: 86%
“…In this sense, response surface methodology (RSM) is suitable to reduce the number of experiments required to assess the factors involved in a process and their interactions, generating mathematical models and needing less time. RSM has been successful applied in the development, improvement, and optimization, in conjugation with desirability function of different composite flour formulations (Codină & Mironeasa, ; Kurek et al, ; Marcin, Jarosław, Monika, & Agnieszka, ; Mironeasa, Codină, & Mironeasa, ), describing the relationships between responses and factors and highlighting the effect of factors, alone or in combination, on dough bread rheological characteristics, dough microstructure, or baked products properties. Conversely, during the last years have seen new tools of data analysis in the area of artificial intelligence, like Artificial Neuronal Networks (ANNs), which offer real advantages over conventional modeling (Funes, Allouche, Beltrán, & Jiménez, ).…”
Section: Introductionmentioning
confidence: 99%
“…() also reported that the DT decreased with the addition of extruded wheat flour. DT is related to the gluten content and WA (Codinä & Mironeasa, ). The addition of BRF and EBRF led to a dilution of gluten which decreases the quantity and quality of protein and hence, the dough became weaker.…”
Section: Resultsmentioning
confidence: 99%
“…Fluorescein detects starch and rhodamine B proteins from the dough system. The EFLM images were analyzed using ImageJ (v. 1.45, National Institutes of Health, Bethesda, MD, USA) software according to Peighambardoust et al [44] and Codină and Mironeasa [45,46].…”
Section: Microstructure Of Flour Composite Doughmentioning
confidence: 99%